Government Spending in Uncertain and Slack Times: Historical Evidence for Larger Fiscal Multipliers - Pascal Goemans (ZBW - Leibniz Information Centre for Economics, 2020)
We investigate whether US government spending multipliers are higher during periods of heightened uncertainty or economic slack as opposed to normal times. Using quarterly historical data and local projections, we estimate a cumulative one-year multiplier of 2 during uncertain periods. In contrast, the multiplier is about 1 in times of high unemployment and about 0:5 - 0:7 during normal times. While we find positive employment effects in economic slack as in uncertain times, two transmission channels can explain the higher multipliers in the latter: greater price exibility leading to short run in ation (lowering the real interest rate) and diminishing risk premiums.
Keywords: E62; 330; Fiscal policy; government spending; fiscal multiplier; uncertainty; economic slack; local projections; historical data